Pipistrellus kuhlii ... - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus kuhlii (Kuhl, 1817) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Least Concern - LC (Rondinini et al., 2013). This species was detected several times up to 1450 m a.s.l., nearby the locality of Palanfrè (Vernante), where single males were also captured on 2 nd and 12 th August, 2006. A reproductive roost located in a roof was found in Entraque (850 m a.s.l.). Here 30 individuals and 42 individuals were respectively counted exiting the roost on 23 rd August, 1995 and on 12 th July, 2009. ... : Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI: 10.4081/nhs.2016.254, http://zenodo.org/record/12523731 ...